Modeling the dynamic kinetics of microbial disinfection with dissipating chemical agents—a theoretical investigation - Peleg, Micha (Appl Microbiol Biotechnol, 2021)
ABSTRACT: The most notable microbial survival models of disinfection kinetics are the original and modified versions of the static Chick-Watson-Hom’s (CWH) initially developed for water chlorination. They can all be viewed as special cases of the Weibull survival model, where the observed static curve is the cumulative form (CDF) of the times at which the individual targeted microbes succumb to the treatment. The CWH model time’s exponent is the distribution’s shape factor, and its concentration-dependent rate parameter represents the distribution’s scale factor’s reciprocal. Theoretically, the concentration- dependence of the Weibull model’s rate parameter need not to be always in a form of a power-law relationship as the CWH model requires, and two possible alternatives are presented. Apart from being chemically reactive, most chemical disinfectants are also volatile, and their effective concentration rarely remains constant. However, the published dynamic versions of the original CWH model are mathematically incongruent with their static versions. The issue is nonexistent in the dynamic version of the Weibull or other distribution-based models, provided that the momentary inactivation rate is expressed as the static rate at the momentary concentration, at the time that corresponds to the momentary survival ratio. The resulting model is an ordinary differential equation (ODE) whose numerical solution can describe survival curves under realistic regular and irregular disinfectant dissipation patterns, as well as during the disinfectant dispersion and/or its replenishment. KEY POINTS: • The Chick-Watson-Home models are treated as special cases of the Weibull distribution. • Dynamic microbial survival curve described as ordinary differential equation solution. • Survival rate models of disinfectant dissipation and replenishment patterns presented. GRAPHICAL ABSTRACT: [Image: see text]